Promoting the access and adoption of climate smart agriculture innovations through capacity building in Makindu Sub-County Kenya. - Nduah, Alex; Nzuki, Esther; Ogutu, Liz; Waswa, Boaz (2024)
AICCRA's collaboration with Kimatwa Women SACCO in Makueni County has revolutionized farming practices through CSA access and adoption by small-scale women farmers. Key CSA innovations scaled out include drought-tolerant crop varieties, Conservation Agriculture (CA), and bundling of CSA with climate information services (CIS). The "Mother-Baby Demo" farm model facilitated localized peer learning, enabling over 1,100 farmers to improve yields and enhanced resilience to climate change. The partnership activated a revolving seed scheme and co-designed the ‘Rip 1, Get one free’ tractor ripping services. These approaches boosted the adoption of CSA innovations coupled by Trainer of Trainers (ToTs) capacity-building arrangements where trained farmers act as trainers in their local communities. For the first time in seven years, the farmers harvested beans from their farms after adopting the CSA innovations. The project has simultaneously promoted gender inclusion, financial empowerment, and community-led leadership, creating a sustainable framework for scaling smart climate agriculture innovations.